Seyma-Turbino Metalworking and Microtechnics: A Game of Scale - Yu. I. Mikhailov (Вестник Кемеровского государственного университета, 2022)
Along with ordinary utilitarian things, Seymа-Turbinо casters made technically advanced products devoid of pragmatic functions. Miniature copies of full-size prestigious products were found in graves and shrines. Probably, communities of metalworkers treated these miniature tools as material symbols of their group identification. Numerous finds made in Petrovka, Sintashta, and Seymа-Turbino archeological sites mean that these metal miniatures were in high demand. Low-rank metal workers might have been buried with miniature samples of less technologically advanced tools. Full-size sophisticated tools, as well as their miniature copies in children's graves, could symbolize individual status. Miniature artistic castings that served as pommels on massive curved knives marked the prestigious status of this type of weapon and symbolically equated it with the Tools of the Creation. The figurines that adorned the Seyma-Turbino weapon not only emphasized its impressive size, but also gave the owners of these perfect products a higher social status. The miniature sculpture, which adorned only some of the Seyma-Turbino metal products, individualized serial samples. Thus, the microtechnics reflected not only the new possibilities of Seyma-Turbino metalworking, but also the regulatory requirements for the design of prestigious metal products. The renewal of the material ambiance was caused by the spread of serial products, the so-called quick things. It reflected the need to strengthen the connection between the owner and the possession, which was inherent to individual single-piece production